Conceptual metaphors about Chilean education and students represented by 2006-2018 online English-speaking newspapers (Foro de Educacion, 2021)
This investigation aims to find how Chilean education is perceived by 69 English-speaking online newspaper articles from 12 different countries. A qualitative study coherent with metaphoric analysis was carried out to identify metaphors about education and students. Conceptual metaphors found in the 99 fragments taken from these news articles are organized into two dimensions. Each dimension deals with a different topic related to education in Chile and how it is represented by online media: Chilean education system, and student role and education conflict. Most of the newspapers scrutinized focused on the commercial and conflictive side of Chilean education, making the categories of Commercialism and War the most frequent ones. The most mentioned topic was the student conflict as the main subject of analysis. Chilean education can be defined as in conflict due to the contrasting viewpoints of the stakeholders involved in it and the inability to come to terms with each party. This unchanging state of affairs has led to ceaseless protests and general unrest from the Chilean population.